2021
DOI: 10.1159/000512675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Movement-Based Mind-Body Interventions on Physical Fitness in Healthy Older Adults: A Meta-Analytical Review

Abstract: <b><i>Introduction:</i></b> Declines in physical fitness can notably affect healthy aging of older adults. Multimodal exercise training regimen such as mind-body interventions (MBIs) has been reported to mitigate these aging-related declines of physical function. This meta-analytical review aimed at pooling the effects of MBIs on physical fitness indices compared to active control (AC) and inactive control (IC) conditions in healthy older adults. <b><i>Methods:</i><… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 54 publications
(118 reference statements)
0
12
0
Order By: Relevance
“…18 studies used RT only, the remainder employed combination RT and AT C: NR 28 (designs NR) Inclusion: > 65 Mean: 70 Range: 65–85 2608 71 NR; lower quality studies had stronger findings (PEDro) da Rosa Orssatto 2019 [ 35 ] To compare change in functional capacity following fast- vs. moderate-velocity lower limb RT in older adults PubMed, Scopus, Web of Science to Jan 2019 2003–2019 I: Fast-velocity lower limb RT C: moderate-velocity lower limb RT 15 RCTs Inclusion: ≥60 Range: 64.4–81.6 593 NR Fair (PEDro) Devries 2014 [ 36 ] To determine whether the addition of creatine to RT increased gains in muscle mass, strength, and function in older adults over RT alone. MEDLINE, HealthStar to June 2013 1998–2013 I: RT and Creatine supplementation C: RT and placebo 10 RCTs Inclusion: > 45 Range: 55–71 357 NR; 20% F only, 40% M only Low-moderate (Jadad) Ebner 2021 [ 37 ] To determine the effects of mind-body interventions on physical fitness in healthy community dwelling older adults. Web of Knowledge, PubMed, SPORTDiscus to Nov 2019 2005–2019 I: Yoga, Qi Gong, Tai Chi, Pilates C: Active and inactive controls 30 RCTs Inclusion: ≥65 Mean: 71.2 2792 37 3% poor 17% fair 63% good 17% excellent (PEDro) Elboim-Gabyzon 2021 [ 38 ] To explore the effectiveness of high-intensity interval training for reducing fall risk factors in older adults.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…18 studies used RT only, the remainder employed combination RT and AT C: NR 28 (designs NR) Inclusion: > 65 Mean: 70 Range: 65–85 2608 71 NR; lower quality studies had stronger findings (PEDro) da Rosa Orssatto 2019 [ 35 ] To compare change in functional capacity following fast- vs. moderate-velocity lower limb RT in older adults PubMed, Scopus, Web of Science to Jan 2019 2003–2019 I: Fast-velocity lower limb RT C: moderate-velocity lower limb RT 15 RCTs Inclusion: ≥60 Range: 64.4–81.6 593 NR Fair (PEDro) Devries 2014 [ 36 ] To determine whether the addition of creatine to RT increased gains in muscle mass, strength, and function in older adults over RT alone. MEDLINE, HealthStar to June 2013 1998–2013 I: RT and Creatine supplementation C: RT and placebo 10 RCTs Inclusion: > 45 Range: 55–71 357 NR; 20% F only, 40% M only Low-moderate (Jadad) Ebner 2021 [ 37 ] To determine the effects of mind-body interventions on physical fitness in healthy community dwelling older adults. Web of Knowledge, PubMed, SPORTDiscus to Nov 2019 2005–2019 I: Yoga, Qi Gong, Tai Chi, Pilates C: Active and inactive controls 30 RCTs Inclusion: ≥65 Mean: 71.2 2792 37 3% poor 17% fair 63% good 17% excellent (PEDro) Elboim-Gabyzon 2021 [ 38 ] To explore the effectiveness of high-intensity interval training for reducing fall risk factors in older adults.…”
Section: Resultsmentioning
confidence: 99%
“…Included reviews reported on several types of interventions, with some reporting separate results for more than one intervention type. Most reviews focused on exercise or PA only ( n = 53) [ 26 35 , 37 40 , 42 , 44 , 45 , 47 , 49 – 75 , 77 , 78 , 80 – 84 , 86 ], while others included exercise with nutritional supplements ( n = 9) [ 25 , 36 , 41 , 43 , 46 , 48 , 76 , 79 , 85 ]. No reviews included group-based nutrition interventions alone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting disuse muscle atrophy further limits their independence, eventually forcing them to bed and hospitalization for long periods [2][3][4]. In addition to nutritional and pharmacological treatments, physical exercise at home is useful to counteract muscle atrophy in these persons [5][6][7][8][9].…”
mentioning
confidence: 99%